Adversity Quotient and College Student’s Learning Plateau and Its Implications in Guidance and Counseling Services - Reza Tririzky; Khairani Khairani; Zadrian Ardi (Jurnal Neo Konseling, 2020)
Adversity Quotient (AQ) is basically beneficial for human life, including college students. Having a high AQ will certainly make college students more resilient in the face of difficulties and obstacles that occur in connection with the educational process that they undergo so as to be able to prevent various difficulties that arise such as learning plateau in the educational process being undertaken by college students in various levels of education. The purpose of this study is to look at the possibility of increasing Adversity Quotient (AQ) to reduce student's learning plateau. This research is qualitative research in the form of library research using secondary data obtained from various sources such as books, literature, and articles published in journals. Then the data are analyzed using content analysis or content to understand the existing content of the collected data and integrate it in writing. It is known that there is a possibility of increasing the AQ which will be useful to reduce the student's learning plateau, through Guidance and Counseling services especially Group Guidance services. Integrating other services in the Guidance and Counseling services is also important to get a complete picture of the conditions faced by clients or students.